Religiosity and Environmentally Friendly Behavior of Millennial Muslim Consumers - Rafsanjani, Elfas; Asnawi, Nur (MEC-J (Management and Economics Journal), 2020)
The purpose of this study is to investigate the impact of attitudes, subjective norms and religiosity on consumer intentions to support government policies on environmentally friendly behaviour. Based on a direct survey of 100 Muslim student respondents then analyzed using multiple linear regression, it was found that attitudes, subjective norms and religiosity as determinants of Muslim consumer intentions in supporting government policies on environmentally friendly behaviour, namely paid plastic bag policies. Finally, an important finding from this study is the contribution of subjective norms as the dominant determinant that influences the Muslim consumer's intention to support government policies to behave in an environmentally friendly manner by being willing to support a paid plastic bag policy.